Hearing prevention program: how speech-language pathologists and audiologists work in the occupational health area - Claudia Giglio de Oliveira Gonçalves; Fabiane Rodrigues dos Santos; Lucas Schmidt; Jair Mendes Marques (Revista CEFAC, 2020)
ABSTRACT Objective: to characterize speech-language pathologists/audiologists and their interventions in the occupational health area, regarding the Hearing Prevention Program (HPP). Methods: a cross-sectional, quantitative study with 74 speech-language pathologists/audiologists from several regions of Brazil, working in the areas of Occupational Health and Audiology. The participants answered a questionnaire on their professional and educational profile, as well as on their work related to the HCP components. For data analysis, statistical procedures were used (Chi-Square Test and the test of difference in proportions, at the significance level of 0.05 - 5%), in relation to the variables of gender, age, job position, time since their graduation and academic training in occupational safety and health. Results: the speech-language pathologists/audiologists, mostly women, who reported performing the HPP, were older than 30 years, had specific postgraduate courses, but still had doubts about the Program implementation, they worked for companies with over 1,000 employees, disregarding their employment status, performing interventions, such as: hearing management and guidance on the correct use of ear protectors. Conclusion: a high number of speech-language pathologists in the Occupational Health area have not developed a complete hearing conservation program to this date.